Oestrogen receptor ERα and ERβ agonists ameliorate oxidative brain injury and improve memory dysfunction in rats with an epileptic seizure. Issue 12 (15th November 2019) - Koyuncuoğlu, Türkan; Arabacı Tamer, Sevil; Erzik, Can; Karagöz, Ayça; Akakın, Dilek; Yüksel, Meral; Yeğen, Berrak Ç.
Abstract : New Findings: What is the central question of this study? Could different hormonally active substances, including oestrogen receptor (ER) agonists, protect against oxidative brain damage and memory impairment induced by a single epileptic seizure in rats? If so, which signalling mechanisms are involved in their anti‐inflammatory effects? What is the main finding and its importance? Chronic administration of oestrogen, progesterone, ER modulators/agonists or blockade of testosterone exhibited anti‐inflammatory and antioxidant actions on single seizure‐induced neuronal injury, while ER agonists additionally improved memory function and up‐regulated CREB signalling and hippocampal GABA(A)α1 receptor density, suggesting that ERα or ERβ receptor activation may be beneficial in protecting against seizure‐related oxidative brain injury and cognitive dysfunction. Abstract: The susceptibility to epileptic seizures is dependent on sex as well as fluctuations in oestrogen levels, while exogenous oestrogen was shown to have no effect or to facilitate or to inhibit seizure activity. Oestrogen receptors (ERs) mediate antioxidant and anti‐inflammatory actions in several inflammatory models, but the involvement of ERs in seizure‐induced neuronal injury has not been evaluated previously. In order to assess the effects of resveratrol, progesterone, oestradiol (E2), an anti‐testosterone (cyproterone acetate; CPA), a selective ER modulator (tamoxifen; TMX) and ERα/ERβ agonists (propyl pyrazole triol (PPT), diarylpropionitrile (DPN)) on oxidative brain damage and memory impairment due to epileptic seizure, male Wistar rats ( n = 120) received one of the treatment choices either in drinking water or intraperitoneally for 31 days, and epileptic seizure was induced on the 28th day by injection of a single‐dose of pentylenetetrazole (45 mg kg −1 ). The results demonstrate that chronic pretreatment with resveratrol, progesterone, E2, CPA or TMX suppressed most of the inflammatory parameters indicative of oxidative neuronal injury, while treatment with the ER agonists DPN or PPT were found to be even more effective in limiting the oxidative damage. Treatment with DPN resulted in the up‐regulation of cAMP response element‐binding protein (CREB) and brain‐derived neurotrophic factor (BDNF) expression, while PPT up‐regulated expression of CREB without affecting BDNF levels. Moreover, both ER agonists provided protection against seizure‐induced memory loss with a concomitant increase in hippocampal GABA(A)α1‐positive cells. In conclusion, ER agonists, and more specifically ERβ agonist, appear to provide maximum protection against seizure‐induced oxidative brain injury and associated memory dysfunction by up‐regulating the expression of CREB, BDNF and GABA(A)α1 receptors. Abstract :